The foundations of marital life to form a successful family as seen by university youth at Tishreen University “A field study on a sample of fourth-year students as a classroom teacher in the College of Education” - حمدي, لميس (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The development of societies depends on the success of the family, which is based on the foundations of successful marital life, which the spouses carry out in harmony in the basic formation of their personalities, and their awareness of the foundations of marital life to form a successful family, which is considered one of the most important pillars of mental health and successful family relationships with strong ties based on love, affection, respect, and cooperation. It reduces many family disputes, which many studies have attributed to the lack of knowledge and life skills, and the absence of marital and family culture, that is, the lack of knowledge of the foundations of marital life and the basic rules for forming a successful family before marriage to ensure the stability and success of family life. The research aims to identify the opinions of fourth-year university youth, a class teacher in the College of Education at Tishreen University, about the foundations of marital life to form a successful family. To reveal the differences between the average grades of fourth-year students (male grades) in the College of Education at Tishreen University with regard to the foundations of marital life for forming a successful family, according to the variable of gender, and after study and analysis, the research reached the following results: There are no statistically significant differences at the level of significance (a = 0.05) between the average grades of fourth-year students (male grade) in the College of Education at Tishreen University with regard to the foundations of choosing a marital partner among university youth, according to the gender variable. There are no statistically significant differences at the level of significance (a = 0.05) between the average grades of fourth-year students (male class) in the College of Education at Tishreen University with regard to healthy marital relationships among university youth, according to the gender variable. There are no statistically significant differences at the level of significance (a = 0.05) between the average grades of fourth-year students (male grade) in the College of Education at Tishreen University with regard to successful family formation among university youth, according to the gender variable. One of the research proposals is to introduce a study material at the end of the secondary or university stage on the foundations of marriage, marital relations and family life, within the family education, social education, or health education curriculum. And holding youth programs and seminars that address issues of marriage and successful family life, especially freedom of choice, age and cultural compatibility between partners, dealing with affection and respect, avoiding violence in its various forms, and sharing family and educational responsibility